2014
DOI: 10.15669/pnst.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PSF-detector for contaminated areas

Abstract: Hitachi-GE Nuclear Energy, Ltd. has developed the Dose rate meter called "D-phod (Detector for photon dose)" using fiber optics as a radiation sensor to figure out the dose rate of Fukushima area which is contaminated by radioactive materials. D-phod is a tool that can rapidly measure linear or curved dose rate up to 20m along fiber optics. Element technology has already established, however, existing measurement system is unfit to measure environmental dose rate. Therefore, we improved it to be able to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This system consists of a 10-m-long PSF that responds to gamma radiation, light detection units connected to both sides of the PSF, a signal processing unit, and other components50. The system can provide numerical values of the gamma-ray dose rate in air along the 10-m-long PSF at an interval of 0.5 m.…”
Section: Methodsmentioning
confidence: 99%
“…This system consists of a 10-m-long PSF that responds to gamma radiation, light detection units connected to both sides of the PSF, a signal processing unit, and other components50. The system can provide numerical values of the gamma-ray dose rate in air along the 10-m-long PSF at an interval of 0.5 m.…”
Section: Methodsmentioning
confidence: 99%
“…There are a few methods for estimating the gamma-ray source position using the PSOF detector by measuring the time difference, height of pulse, or light power difference in the transmitted path of scintillation light. Using the time difference method, many researchers estimated the position of a gamma ray with FWHMs that were in the range of 3.29-9.12% of the total length of the PSOF [4,15,16,[18][19][20][21][22]. Other researchers used the difference in signal height to estimate the positions of gamma-ray sources.…”
Section: Discussionmentioning
confidence: 99%
“…Soramoto et al [15], Emoto et al [18], Nohtomi et al [19], Chichester et al [20], and Gamo et al [21] estimated the position of the gamma-ray source using the time difference method. Previous experimental results for spatial resolution showed that the FWHMs were in the range of 3.29-9.12% of the total length of the PSOF.…”
Section: Introductionmentioning
confidence: 99%